2021
DOI: 10.3390/jcm10020357
|View full text |Cite
|
Sign up to set email alerts
|

Transient Increase and Delay of Multifocal Electroretinograms Following Laser Photocoagulations for Diabetic Macular Edema

Abstract: Background: The acute physiological changes induced by focal retinal photocoagulation (PC) have been largely unexplored. Methods: This was a case-series study. We recorded multifocal electroretinograms (mfERGs) just before PC, and mfERGs were also recorded 5′, 15′, one hour, 24 h, and one week after the PCs. Transient changes of mfERGs were analyzed in eyes which underwent PCs to treat diabetic macular edema. The mfERGs recorded from the predominantly irradiated area and that from non-irradiated areas were ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…However, both treatment options are unable to heal the condition and only limit the consequential damage induced by VEGF overexpression and CNV formation [ 32 ] and have severe side effects. Laser photocoagulation of the ischemic retina reduces the expression of VEGF caused by ischemia, but the thermal effect of the laser can damage the adjacent retina [ 33 ]. It has been shown that the use of anti-VEGF therapy can induce side effects like thrombosis and infarct and consequently increase the mortality [ 22 , 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, both treatment options are unable to heal the condition and only limit the consequential damage induced by VEGF overexpression and CNV formation [ 32 ] and have severe side effects. Laser photocoagulation of the ischemic retina reduces the expression of VEGF caused by ischemia, but the thermal effect of the laser can damage the adjacent retina [ 33 ]. It has been shown that the use of anti-VEGF therapy can induce side effects like thrombosis and infarct and consequently increase the mortality [ 22 , 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%